The effects of localised fatigue on upper extremity jump shot kinematics and kinetics in team handball - Plummer, H. A.; Oliver, G. D. (Journal of Sports Sciences, 2017)
Absract: Team handball is a popular sport worldwide that requires numerous throws to be made throughout the course of a game. Because of the upper extremity demands of repetitive throwing, it is possible that fatigue can alter the mechanics of a shot. The purpose of this study was to determine the influence of localised fatigue on jump shot kinematics and kinetics. Eleven male team handball players (23.1 ± 3.1 years; 185.1 ± 8.3 cm; 89.7 ± 12.2 kg) volunteered. An electromagnetic tracking system was used to examine the jump shot prior to and following localised fatigue. The fatiguing protocol consisted of throwing a 2.2 kg medicine ball into a rebounder until volitional fatigue. No significant kinematic or kinetic differences were observed following fatigue. Shoulder external rotation was -74.8 ± 14.9° prior to and -79.0 ± 14.7° following fatigue at MER. Scapula, external rotation at ball release (BR) prior to fatigue was -2.2 ± 7.0° and -3.2 ± 11.1° following fatigue. Scapular internal rotation, at maximum shoulder internal rotation (MIR), changed from 18.4 ± 11.2° to 20.4 ± 11.8°. Ball velocity decreased from19.8 m/s to 18.8 m/s (P = 0.12). Accuracy percentage in the pre-fatigue trials was 60.8 ± 14.1% and 52.8 ± 12.7% following fatigue (P = 0.20). While no significant changes were observed, it is possible that other fatiguing protocols that more closely represent the aerobic and throwing demands of the sport may have a greater effect on the kinematics and kinetics of the jump shot.